Salt River [compact disc, unabridged] - White, Randy Wayne (Penguin Audio, 2020)
Marion 'Doc' Ford is sure he's beyond the point of being surprised by his old friend Tomlinson's madcap adventures. But he's stunned anew when avowed bachelor Tomlinson reveals that as a younger man he'd fathered multiple children via sperm bank donations. Thanks to ancestry and DNA websites, Tomlinson's now-grown offspring have tracked him down, seeking answers about their roots. But one of them might have something far more nefarious than a family reunion in mind, and when strange things start happening in Tomlinson's presence, it will be up to Doc to prevent his friend's past sins from turning into deadly present-day dangers.